2010
DOI: 10.1021/nl100747w
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Nanowire Devices in Out-of-Plane Geometry

Abstract: We report the fabrication of arrays of single and multiple out-of-plane nanowire devices on a single substrate, an important step for the fabrication of novel three-dimensional devices and the integration of individually addressable nanowires onto current Si planar technology platforms. Vertical nanowire device fabrication can greatly increase device densities; however integrating such devices into arrays with registry to the substrate requires precise control over the number and position of the nanowires. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Modulating the distribution of the number of particles per patterned feature at a single particle level demonstrates the capabilities of the nanopatterned PEG brushes as a platform for the assembly of Au NPs on surfaces. Previous studies33, 41, 42 showed that confining the substrate‐particle interaction into nanoscopic dimensions leads to immobilization of NPs at specific numbers and orientations. The novelty of nanopatterned PEG brushes is the presence of additional knobs (molecular weight of the brush and size of the particle) to tune the substrate‐particle interaction at the nanoscale.…”
Section: Resultsmentioning
confidence: 99%
“…Modulating the distribution of the number of particles per patterned feature at a single particle level demonstrates the capabilities of the nanopatterned PEG brushes as a platform for the assembly of Au NPs on surfaces. Previous studies33, 41, 42 showed that confining the substrate‐particle interaction into nanoscopic dimensions leads to immobilization of NPs at specific numbers and orientations. The novelty of nanopatterned PEG brushes is the presence of additional knobs (molecular weight of the brush and size of the particle) to tune the substrate‐particle interaction at the nanoscale.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the RTJ units by themselves are tiny units that can be structured and arranged into periodic array (by controlling the VLS growth of SiNWs as demonstrated in previous works,) which will be convenient for precise electric addressing and signal processing. Meanwhile, the Si‐based RTJ units are promising candidates to serve as self‐powered and biofriendly photodetectors to bio tissue environment .…”
Section: Resultsmentioning
confidence: 99%
“…In previous work on the electrostatic assembly of nanoparticles, substrates were left in the nanoparticle solutions overnight to reach equilibrium [9]. However, the electrostatic assembly should be rather fast due to the strong attraction between the negatively charged particles and the positively charged nanopattern.…”
Section: Effect Of the Immersion Time On The Nanopatterningmentioning
confidence: 99%
“…It is often used in conjunction with another functional molecule that repels or prevents the Au NPs from non-specifically depositing on the non-aminosilane patterned areas [10,17,19,20,22]. In other cases, the resist remains on the Si surface to enable easy removal of non-specifically bound Au NPs [9,10].…”
Section: Introductionmentioning
confidence: 99%